STUDI RESTROSPEKTIF PREVALENSI DAN PROFIL PASIEN HERNIA INGUINALIS PADA ANAK DI RSUP DR. M. DJAMIL PADANG TAHUN 2020- 2022 - Mhd Nurhuda; Fidiariani Sjaaf; Yusti Siana; Dian Puspita; Santia Wulan Sari (Nusantara Hasana Journal, 2025)
An inguinal hernia is a condition of protrusion of an intestinal organ into a cavity through a defect or thin or weak part of the wall of the inguinal ring. The material that enters is more often the small intestine, but can also be fatty tissue or omentum. Inguinal hernias account for 75% of all hernias. The comparative incidence of inguinal hernia is 13.9% in men and 2.1% in women. The risk of incidence increases fourfold in patients with a family history of inguinal hernia compared to patients without a family history. The classification of inguinal hernia consists of lateral inguinal hernia, medial inguinal hernia, and pantalone hernia. Planned (elective) herniotomy surgery is the main management after diagnosis to avoid incarceration. This study aims to determine the prevalence and characteristics of Inguinal Hernia in children at RSUP.DR.M.Djamil Padang in 2020-2022. This research method is descriptive observational research. The sample in this study were patients who had been diagnosed with inguinal hernia in children at DR. M. Djamil Padang Hospital, selected using simple random sampling technique. Research data were obtained from medical records of 46 patients who met the inclusion criteria. The results showed that the most gender was male  with 40 people (87%) inguinal hernia in children. Based on age, the age group 0-1 year of inguinal hernia patients in children is higher at 58.7%. All samples suffered from lateral inguinal hernia (100%). All patients had no family history (100%). The location of inguinal hernia was mostly unilateral on the right side, 69.9%.